PENGARUH PENAMBAHAN SERAT BAJA TERHADAP SIFAT MEKANIS REACTIVE POWDER CONCRETE - shandy trisakti paiding lewa; Patria Kusumaningrum (Universitas Trisakti, 2020)
As urban growth increase, massive high-rise building construction become a critical solution. In high-rise building, column base may be subjected to very high axial load from the upper stories and may experience very large moment due to the lateral loads. As a result, the column base requires a great deal amount of reinforcement which make it very cramped. In order to prevent honeycomb as the reinforcement gap is narrow yet difficult to provide sufficient vibration during concrete casting, high performance concrete (HPC) may be the solution. One of the HPC innovations is Reactive Powder Concrete (RPC). RPC is a self-compacting type of HPC contains well graded fine and super fine aggregates with cement and pozzolanic material to strengthen the Interfacial Transition Zone (ITZ) between the mortar matrix and fine aggregates. RPC may achieve high compressive strength as the mix uses low water to cement ratio, thus it introduces less void and no coarse aggregates, thus ITZ is stronger. RPC has similar characteristic as concrete, with its brittle behaviour. To avoid the brittle failure of RPC, in this study steel fibers are added into the RPC mixture. This research is conducted to examine the effectiveness of using steel fibers on the mechanical properties of Steel Fiber Reactive Powder Concrete (SFRPC). The steel fiber is aimed to increase ductility of tensile strain hardening condition by its multiple crack-bridging behavior.